Wide-field VLBI observations of M31: A unique probe of the ionized interstellar medium of a nearby galaxy - Morgan, John S.; Argo, Megan K.; Trott, Cathryn M.; Macquart, Jean-Pierre; Deller, Adam; Middelberg, Enno; Miller-Jones, James; Tingay, Steven J. (Institute of Physics Publishing, Inc., 2013)
The Very Long Baseline Array was used at 1.6 GHz to observe a target field 50' in diameter including the core of M31. Novel very long baseline interferometry correlation techniques were used to observe 200 sources simultaneously, of which 16 were detected. We classify all 16 as background active galactic nuclei based on their X-ray properties and arcsecond- and mas-scale morphology. The detected sources were then analyzed for evidence of scatter-broadening due to the ionized interstellar medium (ISM) of M31. The detection of a compact background source only 0.25 kpc projected distance from M31* places a constraint on the extent of any extreme scattering region associated with the center of M31. However, the two sources closest to the core show evidence of scatter broadening consistent with that which would be seen for a compact source if it were observed through the inner disk of our Galaxy, at the inclination of M31. We interpret this as a detection of the ionized ISM of M31 along two lines of sight. With the increases in bandwidth and sensitivity envisaged for future long-baseline interferometers, this should prove to be a remarkably powerful technique for understanding the ionized ISM in external galaxies.